Two new gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) from marine fishes off the northern coast of Australia - Moravec, František; Diggles, Ben K (Systematic parasitology, 2014)
Based on light and electron microscopical studies, two new gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) are described from the ovary of marine perciform fishes off the northern coast of Australia (near Darwin): Philometra carangis n. sp. from the bluespotted trevally Caranx bucculentus Alleyne & Macleay (Carangidae) and P. carponotati n. sp. from the Spanish flag snapper Lutjanus carponotatus (Richardson) (Lutjanidae). Philometra carangis is mainly characterised by the length of the spicules (153-189 µm), the presence of a distinct dorsal protuberance consisting of two dorsolateral lamellar parts separated from each other by a smooth median field, a V-shaped mound on the male caudal extremity, a pair of large post-cloacal papillae and the body length of the males (3.22-4.15 mm). Philometra carponotati is distinguished from other congeneric species parasitising lutjanids by the length of the spicules and gubernaculum (225-252 and 99-117 µm, respectively), the absence of a dorsal protuberance on the distal lamellar part of the gubernaculum, the presence of a U-shaped mound on the male caudal extremity, a pair of large post-cloacal papillae and the body length of the male (3.74-4.31 mm). Besides the recently established Philometra zabidii Moravec & Diggles, 2014 (based on a single female), these two newly described nematodes are the only nominal gonad-infecting species of Philometra known to parasitise marine fishes in Australian waters.
Keywords: Animals; velikost těla; Female; ženské pohlaví; druhová specificita; Australia; Gonads; Body Size; gonády; Fishes; Dracunculoidea; Species Specificity; ryby; Austrálie; Aquatic Organisms; Male; vodní organismy; zvířata; mužské pohlaví